Bond Exchanges in the Airline Industry: Analyzing Public Disclosures - Dietrich, J. Richard; Deitrick, James W. (The Accounting Review, 1985)
[A bond exchange is a transaction in which a corporation with an outstanding bond issue offers the current bondholders a new bond in exchange for the outstanding bonds. Bond exchanges affect firms by: (1) altering the cash payments to bondholders, (2) increasing reported earnings, (3) improving financial ratios such as debt/equity, and (4) affecting tax obligations. Although bond exchanges are fairly common, especially in the airline industry, these transactions may be difficult to analyze. This paper reviews the sequence of public disclosures involving an exchange offer, illustrates a present value method for evaluating bond exchanges, and compares the reported results with the "economic" results obtained from this method. Eastern Airlines' 1980 bond exchange is used for illustrative purposes.]